DETEKSI MATA REAL TIME MENGGUNAKAN OPENCV UNTUK ANDROID - Yustika Erliani; Bagus Priambodo (PETIR, 2015)
Right now there has been a lot of developing applications that use the face detection feature. Facedetection itself can be done in various ways, one using the Viola-Jones method, a method thatcombines support vector machines, boosting algorithm, and a cascade classifie. In this researchdesigned an eye detection system by using a Viola-Jones method with OpenCV library. Data fromthis research are in the form of a live video capture using camera smartphone with android os